The Impact of Location and Price on Purchase Decisions for Kencana Park Housing in Kubu Raya Regency (West Kalimantan) - Mulanda, Yunike; Kurniasari, Fita (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
This study analyzes the impact of Location and Price on Purchase Decisions for Kencana Park housing in Kubu Raya Regency. Kencana Park offers strategic accessibility, being close to Transmart, Qubu Resort, Sekolah Tinggi Bahasa Bersama, Supadio Airport, and several universities in Pontianak. The housing also features PDAM, 24-hour security, CCTV, playgrounds, commercial areas, wide roads, and green spaces. Its specifications include reinforced concrete foundations, lightweight steel roof frames, metal sheet roofs, aluminum windows, ceramic floors, and IMB-certified property status. Using an associative approach, the study surveyed 79 respondents, analyzing data through multiple regression analysis with SPSS 25. Tests conducted include validity, reliability, normality, linearity, and multicollinearity. Hypothesis testing using t-test and F-test confirmed that Location and Price significantly and positively influence Purchase Decisions, both individually and collectively.